Formation of a phosphate conversion coating on bioresorbable Mg-based metallic glasses and its effect on corrosion performance. (December 2017) - Miskovic, David M.; Pohl, Katharina; Birbilis, Nick; Laws, Kevin J.; Ferry, Michael
Abstract: Ternary Mg-Zn-Ca metallic glasses show promise as a bioresorbable implant material. Their susceptibility to relatively rapid corrosion rates, however, requires new ways to reduce their initial rate of corrosion post-implantation. To this end, the application of a simple phosphate conversion coating was studied on Mg66 Zn30 Ca4 to determine the metallic glasses impact on coating development. A model for coating growth is proposed. The results demonstrate corrosion resistance can be improved by an order of magnitude in simulated body fluid, with a significant reduction in anodic kinetics. Furthermore, the mechanical reliability under a compressive load is improved two-fold, despite substrate relaxation due to coating.